Assessment of synovial vascularization by power Doppler ultrasonography in TMJ internal derangements treated arthroscopically - VAROL, ALTAN (CHURCHILL LIVINGSTONE, 2008)
Our aim was to evaluate the effect of arthroscopic lysis and lavage of the temporomandibular joint (TMJ) oil synovial microvascularisation by comparing preoperative and postoperative grades measured by power Doppler ultrasonography (US). We Studied 22 patients with hypomobility, clicking, and pain in the TMJ. Power Doppler US were obtained preoperatively to assess the presence of synovial microvascularisation, and arthroscopic lysis and lavage were done after conservative treatment had proved unsuccessful. The severity of synovitis was assessed arthroscopically. The postoperative power DopplerUS scans were obtained 2 months later. Other arthroscopic variables were roofing, adhesions, chondromalacia, clicking, and pain. Arthroscopic synovitis with varying degrees of synovial vascularisation was detected in all patients. Pain scores decreased considerably during the postoperative period. We conclude that power Doppler US is a good technique for the assessment of synovial changes by microvascularisation. Arthroscopy of the TMJ reduces synovial vascularisation. (c) 2008 The British Association of Oral and Maxillofacial Surgeons. Published by Elsevier Ltd. All rights reserved.
Keywords: TMJ synovitis; Arthroscopy; Synovial vascularisation; Power Doppler ultrasonography; TEMPOROMANDIBULAR-JOINT; RHEUMATOID-ARTHRITIS; DIAGNOSIS; OSTEOARTHRITIS; ACCURACY; INFLAMMATION; INVOLVEMENT; SONOGRAPHY; DISORDERS; DENSITY